Reduced urine volume and changed renal sphingolipid metabolism in P2ry14-deficient mice - Baalmann, Fabian; Brendler, Jana; Butthof, Anne; Popkova, Yulia; Engel, Kathrin M.; Schiller, Jürgen; Winter, Karsten; Lede, Vera; Ricken, Albert; Schöneberg, Torsten; Schulz, Angela (Frontiers in Cell and Developmental Biology, 2023)
The UDP-glucose receptor P2RY14, a rhodopsin-like G protein-coupled receptor (GPCR), was previously described as receptor expressed in A-intercalated cells of the mouse kidney. Additionally, we found P2RY14 is abundantly expressed in mouse renal collecting duct principal cells of the papilla and epithelial cells lining the renal papilla. To better understand its physiological function in kidney, we took advantage of a P2ry14 reporter and gene-deficient (KO) mouse strain. Morphometric studies showed that the receptor function contributes to kidney morphology. KO mice had a broader cortex relative to the total kidney area than wild-type (WT) mice. In contrast, the area of the outer stripe of the outer medulla was larger in WT compared to KO mice. Transcriptome comparison of the papilla region of WT and KO mice revealed differences in the gene expression of extracellular matrix proteins (e.g., decorin, fibulin-1, fibulin-7) and proteins involved in sphingolipid metabolism (e.g., small subunit b of the serine palmitoyltransferase) and other related GPCRs (e.g., GPR171). Using mass spectrometry, changes in the sphingolipid composition (e.g., chain length) were detected in the renal papilla of KO mice. At the functional level, we found that KO mice had a reduced urine volume but an unchanged glomerular filtration rate under normal chow and salt diets. Our study revealed P2ry14 as a functionally important GPCR in collecting duct principal cells and cells lining the renal papilla and the possible involvement of P2ry14 in nephroprotection by regulation of decorin.